Relationship between Anxiety, Depression, Trait Mindfulness and Psychological Well-being in People with Atopic Dermatitis: Theoretical Model and its Initial Test - Tamašauskienė, Goda; Kairys, Antanas (Psichologija, 2024)
People with atopic dermatitis (AD) have lower psychological well-being and experience symptoms of anxiety and depression, which are more prominent in the more severe form of the disease. Recent years have shown attempts to address psychological aspects of the disease, such as strengthening trait mindfulness (TM), which may be important for the successful management of AD. This study aims to propose a theoretical model identifying factors predicting psychological well-being in people with AD and to conduct initial empirical testing of this model. Participants were 52 adults aged 18-49 years with AD (84.6% women and 13.5% men). Instruments: Patient-Oriented Eczema Measure (POEM), Beck Anxiety Inventory (BAI), Beck Depression Inventory-II (BDI-II), Supplementary Lithuanian Psychological Well-being Scale (LPGS-P), and Five Facet Mindfulness Questionnaire (FFMQ). Correlational analysis was used to examine the relationships between the variables. The results revealed that anxiety and depression were negatively correlated with TM and psychological well-being, while TM was positively correlated with psychological well-being. TM plays an important role in predicting psychological well-being in people with AD.
Keywords: atopic dermatitis; anxiety; depression; trait mindfulness; psychological well-being